(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Accurate to classic grounded hypothesis, utilizing aGlaserian approach, this research was dependent upon a research area not aninquiry (Glaser & Strauss, 1967). The research area was Ells enteringspecial education from a social work perspective. Six sizes of Ells enteringspecial education were analyzed in the study: needs of Ells; captivatingfamilies of Ells; community associations; expert setting; special educationmethodology; and social work.